Impact of maternal and postnatal zinc dietary status on the prostate of pubescent and adult rats - Camora, Lucas F. [UNESP]; Silva, Ana Priscila G.; Santos, Sérgio A.A. [UNESP]; Justulin, Luis A. [UNESP]; Perobelli, Juliana E.; Barbisan, Luis Fernando [UNESP]; Scarano, Wellerson R. [UNESP] (Wiley, 2017)
Zinc is important for cell physiology and alteration of its levels during development can modulate a series of biological events. The aim of this study was to investigate whether dietary zinc deficiency or supplementation during morphogenesis and early postnatal development could interfere in prostate maturation. Pregnant rats were exposed to a standard diet (NZ:35 mg Zn/kg chow), low-zinc diet (LZ:3 mg of Zn/kg chow) and zinc-supplemented diet (HZ:180 mg/Kg chow) from gestational day 10 (GD10) through postnatal day 21 (PND21). After weaning, male offspring were divided into three groups that were submitted to the same food conditions as their mothers until PND53. The animals were euthanized at PND53 and PND115. The ventral prostate was removed, weighed and its fragments were subjected to histological, western blot and zymography analysis. PND53: body and prostate weight were lower in LZ compared to NZ; the epithelial compartment was reduced while the stromal compartment was increased in LZ compared to NZ; there was an increase in the amount of collagen and reduction in AR and SIRT1 expression in LZ compared to NZ. PND115: body weight was lower in LZ compared to NZ and prostate weight was similar among the groups; peripheral physiological hyperplasia was observed, as well as an increased epithelial proliferation index and reduced PAR4 expression in LZ and HZ compared to NZ. Zinc deficiency during prostate morphogenesis and differentiation is potentially harmful to its morphology, however, by restoring the standard dietary environment, the gland responds to the new microenvironment independent of the previous dietary condition.
Keywords: fetal programming; pre puberty treatment; prostate development; puberty; stromal remodeling; zinc deficiency